COMMUNITY PARTICIPATION IN PAYING LAND AND BUILDING TAXES IN LUNJEN VILLAGE DEAD STONE DISTRICT ENREKANG REGENCY - Ainun, Nur Fitra; Aslinda, Andi; Sakawati, Herlina (Universitas Negeri Makassar, 2025)
This study aims to find out how community participation and what factors affect community participation in paying Land and Building Tax (PBB) in Lujen Village, Buntu Batu District, Enrekang Regency. The research methods used are qualitative research and data collection techniques, namely observation, interviews and documentation. The results of the study show that community participation in paying Land and Building Tax (PBB) in Lunjen Village, Buntu Batu District, Enrekang Regency is still low, due to several factors, namely the level of education, employment and income and the length of stay so that it affects the community on the importance of paying Land and Building Tax (PBB) Therefore, it is hoped that tax officers and taxpayers can increase each other's self-awareness and do more often socialization of the importance of paying Land and Building Tax (PBB) in Lujen Village, Buntu Batu District, Enrekang Regency